Forming the Composition of Underground Coal Gasification Products in the Simulation of Various Heat and Mass Transfer Conditions in the Coal Seam; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Masanik A. S. (2016, 2016)
Title screen